Analisis Pengaturan Inverter Terhadap Unjuk Kerja Mesin Planer Bambu V2 Dalam Menghasilkan Serutan Bambu Laminasi - Silvano Virgio Prasta Prasta; Ignatius Aris Hendaryanto; Budi Basuki; Radhian Krisnaputra; Sugiyanto; Inggar Septhia Irawati (P3M Politeknik Negeri Cilacap, 2024)
Planer bamboo machine V2 is a machine used to flatten the top and bottom surfaces of bamboo slats. This machine was made to overcome problems with existing machines in the form and long times of drawstring. An inverter is added to set the rotational speed roller. This study analyzes the effect of a combination of the top and bottom cutting speeds on the rotation speed of roller whose rotation speed was set at frequencies of 10, 20, 30, 40, and 50 Hz. The purpose of the study is to determine the effect of inverter frequency settings on the results of bamboo drawstring. Based on the analysis performed, the appropriate combination for the performance planer bamboo machine is by setting the inverter frequency to 20 Hz with a production result in a day of 54,54 slats drawstring with long of slats 2 meters, with a total power consumption of 2,483 kWh in one hour.